Analysis of the Implementation of Active, Creative, and Collaborative Learning Models in Arabic Language Instruction at Madrasah Aliyah: Teachers’ and Students’ Perspectives - Alma Ilmi Nafiatin; Wini Pitriyani (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the implementation of active, creative, and collaborative learning models in Arabic language instruction at Madrasah Aliyah from the perspectives of teachers and students. It also seeks to identify the supporting and inhibiting factors in applying these learning models, as well as the alignment between the instructional strategies planned by teachers and the learning experiences perceived by students within the active, creative, and collaborative framework. This research employs a descriptive qualitative approach to provide an in-depth depiction of how the active, creative, and collaborative learning models are applied in Arabic language teaching at Madrasah Aliyah. Data were collected through interviews, classroom observations, and documentation, supported by secondary sources such as lesson plans and relevant literature. The data were analyzed using an interactive model through the stages of data reduction, data display, and conclusion drawing. The findings present a comprehensive overview of teacher strategies, student responses, and classroom dynamics. The study reveals that active, creative, and collaborative learning at Madrasah Aliyah is implemented through discussions, dialogues, varied media, and group work. Teachers play a crucial role in creating engaging and adaptive learning environments, while students generally respond positively despite differing levels of ability. Supporting factors include teacher competence and student motivation, whereas the barriers involve limited time, inadequate facilities, and classroom dynamics. Teacher flexibility emerges as the key to ensuring effective learning implementation.